The Ds1 Transposon Provides Messages That Yield Unique Profiles of Protein Isoforms and Acts Synergistically With Ds to Enrich Proteome Complexity via Exonization. (22nd February 2017) - Charng, Yuh-Chyang; Hsu, Lung-Hsin; Liu, Li-yu Daisy
In exonization events, Ds1 may provide donor and/or acceptor sites for splicing after inserting into genes and be incorporated into new transcripts with new exon(s). In this study, the protein variants of Ds1 exonization yielding additional functional profile(s) were studied. Unlike Ds exonization, which creates new profiles mostly by incorporating flanking intron sequences with the Ds message, Ds1 exonization additionally creates new profiles through the presence or absence of Ds1 messages. The number of unique functional profiles harboring Ds1 messages is 1.3-fold more than that of functional profiles without Ds1 messages. The highly similar 11 protein isoforms at a single insertion site also contribute to proteome complexity enrichment by exclusively creating new profiles. Particularly, Ds1 exonization produces 459 unique profiles, of which 129 cannot be built by Ds . We thus conclude that Ds and Ds1 are independent but synergistic in their capacity to enrich proteome complexity through exonization.